Selecting Optimum Dimensions for a Three-Phase Horizontal Smart Separator for Khor Mor Gas-Condensate Processing Plant - Sulaiman, Fenk A.; Sidiq, Hiwa (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The Khor Mor gas-condensate processing plant in Iraq is currently facing operational challenges due to foaming issues in the sweetening tower caused by high-soluble hydrocarbon liquids entering the tower. The root cause of the problem could be liquid carry-over as the separation vessels within the plant fail to remove liquid droplets from the gas phase. This study employs Aspen HYSYS v.11 software to investigate the performance of the industrial three-phase horizontal separator, Bravo #2, located upstream of the Khor Mor sweetening tower, under both current and future operational conditions. The simulation results, regarding the size distribution of liquid droplets in the gas product and the efficiency gas/liquid separation, reveal that the separator falls short of eliminating all liquid droplets of specified sizes from the gas phase to meet efficiency requirements, weather with or without a mist extractor. Consequently, an analysis of various structural parameters of the vessel is undertaken to determine their impact on the carried-over liquid mass flow rate and the vessel’s gas/liquid efficiency. The findings recommend a new design concept termed the "smart separator" for Bravo #2, applicable to both current and anticipated operational scenarios. The smart separator demonstrates a remarkable enhancement in gas/liquid separation efficiency, showcasing improvements of 21.31% and 24.02% under existing and future operating conditions, respectively. This innovative design proves effective in controlling liquid carry-over and maintaining high-efficiency levels, even as vessel inlet flow rates increase over time, thus preventing foaming phenomena in downstream processes caused carried-over liquids.